A collaborative planning method of distribution network including EV charging piles and Distributed Generations. Issue 1 (January 2021) - Yang, Haiyue; Liu, Dong; Yu, Lu; Liu, Eryong; Mei, Xiaohui; Wang, Shouxiang
Abstract: With the growing penetration rate of distributed generations (DGs) and large number of unordered charging electric vehicles (EVs), the distribution network (DN) is facing more challenges than before. Therefore, the DN planning integrated of EVs and DGs is the primely problem. Firstly, an traffic network model and a distributed power supply output model are established to simulate the actual traffic network flow distribution through the principle of user equilibrium flow distribution. Secondly, an improved adaptive free search algorithm is proposed to coordinate site selection planning of EV charging pile and DG considering the factors of economy and users' satisfaction of charging. Finally, taking the modified IEEE 33-node distribution network as an example, the proposed model and algorithm are simulated and verified. The simulation results show that the proposed model and programming method are feasible and effective.